DESIGN AND PERFORMANCE TEST OF JOBS TEARS (COIX LACRYMA JOBI L.) THRESHER MACHINE SOLID CYLINDER ROLL TYPE - Saputra, Ady; Hartanto, Rofandi; ., Warji (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Jobs tears (Coix Lacryma-jobi L.) was a cereal crop that used as high nutrient food and animal feed ingredients. The purpose of this research was to design and test the performance of jobs tears seeds thresher machine of solid cylinder roll type. The machine parts consisted of machines frame, threshing cylinder, jobs tears seeds container, gear transmission, gearbox, and electric motors. Design process of its consisted of structural design and functional design to managed all parts of threshers. This machine was driven by an electric motor. The power and rotational speed of electric motor was 1 HP (1.400) rpm that was transmitted to the gearbox by V-belt and pulley. Speed of electric motor rotation was modified from1,440 rpm to 30 rpm, 38 rpm and 50 rpm by a gearbox with 1:30 ratio. gearbox rotation was transmitted to threshing tool (solid cylinder roll). Rotation of this two solid cylinders roll had a clearance of 6,5 mm that suppressed jobs tears seeds, so the seeds could be separated from the stems. This research resulted the jobs tears seeds thresher machine of solid cylinder roll type. The optimum rotation speed of cylinder was 50 rpm, with loss percentage 79.68% and percentage of good threshed jobs tears seeds 88.57%. This machine had a work capacity of 50,45 kg jobs tears seeds per hour. Keywords: Jobs tears, Thresher of solid cylinder roll type.